Development of Culturally Responsive Physics Learning Materials Based on Batak Cultural Values - Ida Wahyuni; Ratna Tanjung; Rugaya Rugaya; Yeni Megalina; Rizky Agassy Sihombing (Jurnal Penelitian dan Pembelajaran IPA, 2026)
Teachers need well-designed learning materials to achieve instructional objectives. In the P3FIS course, students are required to develop such materials; however, many still lack sufficient understanding to design them effectively. The required components include the Annual Teaching Flow (ATP), semester and annual programs, and teaching modules consisting of teaching materials, learning media, student worksheets, and learning evaluations. Observations of Class B Physics Education students in 2022 indicated that many students come from Batak ethnic backgrounds. To create more contextual and meaningful learning, culturally responsive learning materials grounded in Batak culture are necessary. This study aimed to develop learning materials that are valid, practical, and effective. The research was conducted in the Physics Department at Universitas Negeri Medan using a Research and Development (R&D) approach with the ADDIE model, which includes analysis, design, development, validation, implementation, and evaluation stages. The product developed was a comprehensive set of learning materials validated by three experts. Validation results showed scores of 81.7%, 83.1% and 80.3%, indicating high validity. Practicality results reached 83% in the small group and 93.62% in the large group. The effectiveness test produced an N-gain score of 0.65 (moderate category). Thus, the CRT-based learning materials grounded in Batak culture are considered highly valid, practical, and effective.